MODEL PENGEMBANGAN KEBIJAKAN MUTU DAN KEAMANAN PRODUK PERIKANAN DI PROVINSI JAWA TENGAH - Tri Winarni Agustini; Putut Hai Riyadi (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2008)
Problems encountered on quality and safety of fisheries products covers the variety of product, processing step and also different areas including the use of hazardous material and its source with different characteristics. Such discrepancies are due to several aspects including technical, economic, social culture and institution. It is necessary to conduct study on implementation quality and safety policy of fisheries product in order to produce developed model on quality and safety policy of fisheries products. In overall, this research was aimed to produce recommendations related to development on quality and safety policy of fisheries products at Central Java Province. Important aspects studied during this research were incorrect handling and processing aspect related to utilization of food additives which was considered as one important aspect on quality and safety of the products. Apart from this, social culture, economic, institution and policies aspects were also considered. Research method used was case study. Data were analyzed by qualitative method. There was evidence on utilization of illegal chemical substances (formalin) during handling and processing of fresh fish and salted – dried fish products at 5 research areas, which were Tegal, Pati, Rembang (for fresh fish), and Tegal, Semarang, Pati, Rembang, Cilacap (for salted dried product). Hydrogen peroxide (H2O2) was obviously used on salted- dried fish of Cilacap. Synthetic colour of Rhodamin B was applied on terasi (fermented product) at Pekalongan and Pati. On the other hand, there was no evidence of borax on fish/prawn crackers observed at all research areas. Processing abuse related to utilization of food additives on fresh fish and processed fish products were affected by technical economic, social – culture, institution and policies aspects. Developed model on quality and safety policies of fisheries products can be done by development of alternative natural food additives, implementation of quality standard, improvement on marketing chain especially for chemical man power development, harmonization and control system development involving related institution.